cmr biểu thức sau không phụ thuộc vào x a=(sin^4x+cos^4x -1)(tan^2x+cot^2+2)

By Maya

cmr biểu thức sau không phụ thuộc vào x a=(sin^4x+cos^4x -1)(tan^2x+cot^2+2)

0 bình luận về “cmr biểu thức sau không phụ thuộc vào x a=(sin^4x+cos^4x -1)(tan^2x+cot^2+2)”

  1. Đáp án:

     Ta có:

    +(sin^4x+cos^4x -1)(tan^2x+cot^2+2)

    =(sin^4x+cos^4x -1)[(sinx)^4+(cosx)^4+2(sinx)^2(cosx)^2]/(sinx)^2(cosx)^2

    =[[(sinx)^2+(cosx)^2]^2-2(sinx)^2(cosx)^2-1][(sinx)^2+(cosx)^2]^2/(sinx)^2(cosx)^2

    =[1-2(sinx)^2(cosx)^2-1].1/(sinx)^2(cosx)^2.

    =-2(sinx)^2(cosx)^2/(sinx)^2(cosx)^2.

    =-2

    Giải thích các bước giải:

     

    Trả lời

Viết một bình luận